Experimental Study on the Concrete Surface Preparation Influence to the Tensile and Shear Bond Strength of Synthetic Wraps. (2017) - Tudjono, Sri; Lie, Han Ay; Hidayat, Arif; Purwanto
Abstract: Synthetic sheets are increasing in popularity due to its ease in application, and very high tensile strength characteristics. Previous studies on the utilization of wraps for concrete flexural members resulted in a shear-bond loss in the sheets-to-concrete interface. Although the preparation of concrete surface prior to wrap attachment was in accordance with the product manual, the result was not optimal. Improving the bond could result in an increase of the member's load carrying capacity, so that the capacity of the FRP warp could be optimized. To obtain the most effective surface preparation method, two sets of tests were conducted; firstly to study the tensile-bond behavior, and secondly to investigate the shear-bond response. Four concrete surface preparation methods were explored, consisting of grove configurations with respect to the line of loading. In this research, an independent tensile and shear behavior was assumed. It was found that the commonly used surface preparation was sufficient in tensile, but could lead to de-bonding in shear. The research also concluded that all four proposed methods enhanced the shear-bond; the choice of method is thus influenced by economic aspects, time and application ease. The shear-bond testing method as proposed by the fib code needs to be perfected, since a variation in errors was detected.